The Relationship between Nasal Carriage of Staphylococcus aureus and Surgical Site Infections in a Hospital Center in Morocco - Rachid Flouchi; Abderrahim Elmniai; Abdelaziz Hibatallah; Karim Fahsi; Ibrahim Touzani; Kawtar Fikri-Benbrahim (International Journal of Microbiology)
Background. Surgical site infection is a major public health problem in the world. Nasal carriage is a major risk factor for the development of nosocomial Staphylococcus aureus infection, especially methicillin-resistant Staphylococcus aureus (MRSA). Our work aims to determine the prevalence of Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and the associated risk factors and to evaluate their sensitivity to 27 antibiotics. Methods. A cross-sectional study was carried out on 100 patients, hospitalized in preoperative care of surgery units at the Taza Provincial Hospital Center in the Fez-Meknes region, from January to June 2019. Samples were taken from the patient’s anterior nostril using single-use sterile dry or wet cotton swabs and then analyzed in the Provincial Public Health Laboratory in Taza. The carriage of Staphylococcus aureus was studied by conventional bacteriological methods by spreading nasal swabs on Chapman culture medium, while antibiotic resistance was determined by the Mueller–Hinton agar disc diffusion method according to the recommendations described by the Antibiogram Committee of the French Society of Microbiology 2019 (CA SFM 2019). Results. Of the 84 patients found to be positive, 45.24% had coagulase-positive Staphylococcus aureus and 54.76% had coagulase-negative Staphylococcus. After surgery in the postoperative phase, 16 patients developed surgical site infections, of which two had a negative nasal culture and 14 had positive nasal culture. Among the Staphylococcus aureus-positive patients, 36.84% were colonized by a methicillin-resistant Staphylococcus aureus (MRSA) and 63.16% by a methicillin-sensitive Staphylococcus aureus (MSSA). Of these, 57.14% of MRSA colonized patients developed an infection of the surgical site and 42.85% showed no sign of SSI, while for patients colonized by MSSA, 16.67% developed SSI and 83.33% showed no sign of SSI. Moreover, children were the most affected by MRSA. Concerning antibiotic sensitivity, multiresistance of MRSA to more than 3 antibiotics has been found. Conclusion. To the best of our knowledge, this is the first study carried out in this hospital center with the aim of knowing the prevalence of nasal carriage of Staphylococcus aureus and MRSA and to identify the risk factors in order to prevent infections related to nasal carriage of Staphylococcus aureus and MRSA.